2007
DOI: 10.1038/nature05946
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic growth explained by coincidence between internal and external cues

Abstract: Most organisms use circadian oscillators to coordinate physiological and developmental processes such as growth with predictable daily environmental changes like sunrise and sunset. The importance of such coordination is highlighted by studies showing that circadian dysfunction causes reduced fitness in bacteria and plants, as well as sleep and psychological disorders in humans. Plant cell growth requires energy and water-factors that oscillate owing to diurnal environmental changes. Indeed, two important fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
884
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 615 publications
(974 citation statements)
references
References 38 publications
70
884
3
3
Order By: Relevance
“…In particular, they promote hypocotyl growth during the night while their protein abundance is high. At dawn, growth is stopped as the result of their light-triggered degradation (Nozue et al, 2007). Taking these results into account, we performed our shade-avoidance experiments in continuous light to distinguish between the effects of diurnal cycles versus light quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they promote hypocotyl growth during the night while their protein abundance is high. At dawn, growth is stopped as the result of their light-triggered degradation (Nozue et al, 2007). Taking these results into account, we performed our shade-avoidance experiments in continuous light to distinguish between the effects of diurnal cycles versus light quality.…”
Section: Discussionmentioning
confidence: 99%
“…PIF4 and PIF5 protein levels are specifically reduced in response to R light Recently, it has been shown that PIF4 and PIF5 protein stability depends on light (Nozue et al, 2007), with an Seedlings were grown for 12 days under high R/FR (12 h light, 12 h dark), then transferred to continuous high or low R/FR at dawn on day 13. The expression of all samples relative to Col-0 at dawn was determined according to the method described by Pfaffl (2001), using ACTIN2 as a reference gene.…”
Section: Pif4 and Pif5 Promote The Shade-avoidance Responsementioning
confidence: 99%
“…The circadian oscillator regulates hypocotyl elongation because the accumulation of PIF proteins is restricted to the end of the night (Nozue et al, 2007;Nusinow et al, 2011). Because the circadian oscillator responds to exogenous and endogenous sugars (Dalchau et al, 2011;Haydon et al, 2013) and KIN10 overexpression can lengthen circadian period (Shin et al, 2017), we investigated whether Suc-induced increases in hypocotyl length under short photoperiods involve the circadian oscillator.…”
Section: Kin10 and Tps1 Are Required For Suc-induced Hypocotyl Elongamentioning
confidence: 99%
“…59,60 The gated response to auxin explains the observed growth of plants around dawn in a diurnal photoperiod. 61 At this time of the day, auxin levels and plant responsiveness coincide with increased water turgor pressure and renewal of carbon supply, promoting growth. In summary, the plethora of genes under circadian control and the capacity the clock has on modulating multiple responses through a gating mechanism, highlights the importance of the circadian clock in adjusting the plant to its environment.…”
Section: Light Perception and Signal Transduction To The Clockmentioning
confidence: 99%